Construction Technology for Roadbed and Pavement of Highway Bridge Settlement Section - Liang, YaQiong (Transactions on Engineering and Technology Research, 2024)
In the transition area between highways and bridges, settlement often occurs. Even in the transition zone, small differences in settlement between bridge piers and embankments can easily lead to the occurrence of bridge head jumping events. Bridgehead jumping not only affects the comfort, speed, and safety of driving, but also creates a negative impression on the overall image of highways, shortening the service life of cars. At the same time, it can also affect the efficiency and availability of road traffic, and may even lead to traffic safety accidents. Based on an in-depth analysis of the settlement and deformation mechanism of highway bridge foundations, we have discussed the construction technology of road bridge settlement embankments.